Graphene oxide loaded with tumor-targeted peptide and anti-cancer drugs for cancer target therapy - Ran Li (Nature Portfolio, 2021)
Abstract In the present work, we constructed nanoscale graphene oxide (NGO) as a drug nanocarrier to improve the process of tumor-targeted drug releases, promote cellular uptake and accumulation of chemotherapy drugs in tumor tissues, and reduce the toxic effects of chemotherapy drugs on normal cells. Hence, great stability was obtained in the biological solution. Moreover, we designed an effective nanoparticle system for the doxorubicin (DOX) delivery targeting the oral squamous cell carcinoma (OSCC) by mediating the HN-1 (TSPLNIHNGQKL) through hydrogen and π–π bonds. DOX@NGO-PEG-HN-1 showed significantly higher cellular uptakes and cytotoxicity in OSCC cells (CAL-27 and SCC-25), compared to free DOX. Moreover, HN-1 showed considerable tumor-targeting and competition inhibition phenomenon. As we expected, the nanocarrier showed pH-responsive drug release. In total, our study represented a good technique to construct OSCC-targeted delivery of nanoparticles and improve the anticancer medicines’ efficiency.